MATERIAL CHARACTERIZATION OF SUPERCONDUCTING NANO CRYSTALLINE CERAMIC YSrBiCuO BY THERMAL TECHNIQUES - Isac, Jayakumari; Mony, Anusha; G. Nair, Harikrishnan; Jacob, Reenu; Issac, Sheelakumari; Vinila, V. S.; Rajan, Sam; S. Nair, Anitha; Satheesh, D. J. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The nano-sized ceramic superconducting material YSBCO having perovskite structure was prepared according to the chemical formula by the thermo chemical solid state reaction technique using a high-energy ball milling process through mechanically assisted synthesis. It was characterized by XRD, SEM and EDX. Here the authours studied the thermal characterization using TGA, DTA and DSC.